The Influence of Service Quality Dimensions, Insurance System, and Sincerity on BPJS Patient Satisfaction, Trust, and Loyalty in Indonesian Hospitals - Pratisara Putri, Nadiah Alysia; Pink Berlianto, Margaretha (Dinasti Publisher, 2025)
This study was conducted to determine the effect of service quality, insurance system, and sincerity of medical personnel on the level of satisfaction, trust, and loyalty of outpatients at XYZ Private Hospital. This study involved 450 outpatient BPJS patients. Data collection was carried out by distributing questionnaires containing 45 questions with a Likert Scale of 1-5 based on the judgmental sampling method. Data were analyzed using the SEM PLS method. The results showed that empathy, insurance system, and sincerity had a significant positive effect on patient satisfaction. Reliability had a significant negative effect on patient satisfaction. Assurance and responsiveness did not affect patient satisfaction. In addition, patient satisfaction and trust had a positive and significant effect on patient loyalty. Patient satisfaction had a positive and significant effect on patient trust in XYZ Private Hospital, while tangible assets had a negative and significant effect on loyalty. Assurance, responsiveness and reliability are further evaluated to ensure that resources are not over-utilized on aspects that are considered less important by respondents. Future studies can take a larger population including other Private Hospitals as well as Government Hospitals and record the diagnosis of diseases experienced by participating patients.